Imaging Diagnostics, Biomarkers, and Emerging Trends in Orthopedic Research and Treatment - Trestka, Gabriela; Domino, Wiktoria; Zelik, Urszula; Przygoda, Maria; Śnieżna, Joanna; Stępień, Kamila; Adamczyk, Sabina; Florczak, Wojciech; Włodyka, Jagienka; Dziewic, Jakub; Dzwonnik, Karol (Quality in Sport, 2025)
With an aging population, increasing sports participation, and a rising number of obese individuals, researchers are addressing the growing prevalence of musculoskeletal diseases. Early diagnosis is crucial for effective treatment and disease prevention. Imaging techniques and biomarkers are essential tools in orthopedic diagnostics, providing critical insights into disease progression, treatment efficacy, and clinical outcomes prediction. This paper offers an overview of key imaging modalities, including X-ray, CT, MRI, ultrasonography, scintigraphy, and fluorescence tomography (FLAIR), highlighting their strengths, limitations, and clinical applications. X-ray and CT are commonly used for bone-related issues, while MRI and ultrasonography are invaluable for evaluating soft tissues. Scintigraphy and FLAIR, on the other hand, are particularly effective for detecting metabolic activity and soft tissue changes. Biomarkers, such as those used in osteoarthritis, osteoporosis, joint inflammation, and bone regeneration, complement imaging techniques by enabling early diagnosis, monitoring disease progression, and predicting treatment outcomes. The integration of biomarkers with imaging provides a more comprehensive approach to patient care. Finally, emerging technologies like artificial intelligence, smartphones, 4DCT, and 3D printing of implants are poised to revolutionize orthopedic diagnostics and treatment. These advancements promise greater precision in diagnostics, personalized treatments, and improved patient outcomes, though challenges in implementation and technology adoption remain.